Investigation and probable solution of low end torque dip problem of CAMPRO 1.6L Engine - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur; Alias, Arfah; Farraen, M.A. (Universiti Malaya, 2008)
The main objective of this work is to perform an extensive study on the causes of the torque dip in CAMPRO engine and subsequently to provide the best solution that will improve the performance, reliability as well as production cost. CAMPRO engine is a basic Double Overhead Camshaft (DOHC) which has a capacity of 1597 cc and installed with a total of 16 valves developed by Malaysian car manufacturer PROTON. The CAMPRO engine experiences performance downfall when it reaches at certain rpm. The phenomenon is known as torque dip or torque loss where the output torque is not smooth, consequently formed a dip in the torque curve. The dip which occurs at 2500 – 3500 rpm is mainly influenced by the geometry of the designed intake manifold and valve timing. Analysis is mostly confined on the intake manifold geometry. From the analysis done, two possible solutions were provided viz., Natural Dual Intake Manifold and Continuous Variable Intake Manifold.